A Case Report of Monkeypox in a 4-Year-Old Boy from the DR Congo: Challenges of Diagnosis and Management. (9th April 2020) - Eltvedt, Anna Korsgaard; Christiansen, Michael; Poulsen, Anja
Abstract : Monkeypox (MP) is a rare zoonotic disease that most commonly transmits from bush animals to humans in the Congo Basin of Africa. However, an increase in cases of MP has been observed over the past decades with frequent outbreaks as well as export of the disease out of the African continent. MP belongs to the same genus of viruses as smallpox, the Orthopoxvirus, and vaccination against smallpox gives some protection against MP. With the eradication of smallpox in 1980, vaccination against smallpox has ceased. The resulting decrease of immunity against Orthopoxvirus is thought to be related to the increase in MP cases. Furthermore, closer contact between humans and bush animals could play a role along with the ongoing difficulties of controlling HIV in the same geographical area. MP remains a diagnostic challenge. Lack of knowledge about the disease among health personnel plays an important role, as well as access to diagnostic tools is limited. Treatment of MP is for now symptomatic. We report the case of a 4-year-old boy from the DR Congo with the clinical diagnosis of MP. This case illustrates some of the abovementioned challenges related to the management of MP in the field.